2022
DOI: 10.3390/bs12100354
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Support for the Involvement Load Hypothesis (ILH): A Systematic Review

Abstract: The Involvement Load Hypothesis (ILH) has become a widely used framework for predicting second language (L2) vocabulary learning from task completion. The purpose of this systematic review was to analyze the predictive ability of the ILH in the acquisition of aspects of knowing a word, its application in different target populations, the effective vocabulary learning task types designed based on the ILH, and the occurrence rate of the ILH components in vocabulary learning tasks. We searched IEEE, ERIC, WOS, Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Third, learning academic vocabulary was integrated into the syllabi of the EAP course offered for the participants, and learning vocabulary items inside the classroom and then reviewing those words in self-regulated learning outside the classroom increased the effectiveness of the instructional approach. This affordance of mobile-assisted learning facilitated and promoted the level of the students’ task involvement that is essential for long-term vocabulary development ( Liu and Reynolds, 2022 ). Consequently, considering the importance of academic vocabulary for university students and also significant learning gains observed for mobile-assisted FonFs, it seems that this pedagogical approach can compensate for inadequate coverage of academic vocabulary in EAP programs and facilitate students’ academic literacy development by using the affordances of mobile-assisted learning for extending the vocabulary learning beyond the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, learning academic vocabulary was integrated into the syllabi of the EAP course offered for the participants, and learning vocabulary items inside the classroom and then reviewing those words in self-regulated learning outside the classroom increased the effectiveness of the instructional approach. This affordance of mobile-assisted learning facilitated and promoted the level of the students’ task involvement that is essential for long-term vocabulary development ( Liu and Reynolds, 2022 ). Consequently, considering the importance of academic vocabulary for university students and also significant learning gains observed for mobile-assisted FonFs, it seems that this pedagogical approach can compensate for inadequate coverage of academic vocabulary in EAP programs and facilitate students’ academic literacy development by using the affordances of mobile-assisted learning for extending the vocabulary learning beyond the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mobile-assisted learning might be regarded as a pedagogical intervention to deliver vocabulary learning tasks with high level of involvement. Previous studies indicated that such involvement results in improved vocabulary learning outcomes and also more effective retention of the learned vocabulary items ( Laufer and Hulstijn, 2001 ; Yanagisawa and Webb, 2021 ; Lei and Reynolds, 2022 ; Liu and Reynolds, 2022 ). Additionally, repeated encounters with the target vocabulary items is a crucial factor in L2 vocabulary learning ( Webb and Nation, 2017 ), and mobile-assisted learning environments provide learners with some affordances to recycle the learned items and increase the level of uptake from input.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In essence, the extent to which a new word is remembered depends on the level of cognitive involvement, particularly the mental efforts invested when encountering contextual clues (Keating, 2008;Taheri and Golandouz, 2021). However, prior studies have not reached a consensus on whether external-provided or internal-generated contexts necessitate higher cognitive involvement and elicit greater mental efforts from learners (Zou, 2017;Gohar et al, 2018;Alavinia and Rahimi, 2019;Liu and Reynolds, 2022). Soleimani et al (2015) even suggested that learners appear to engage in similar mental efforts and achieve comparable performance when viewing presented contextual clues compared to generating their contexts, which may be attributed to the fact that EFL learners often prefer high-quality, easily understandable examples to grasp word meanings (Xu, 2006;Webb, 2008).…”
Section: Research Regarding Contextual Clues In Efl Vocabulary Learningmentioning
confidence: 99%
“…Two of these meta-analyses revealed that language learners who engage in tasks with a higher IL achieve greater gains in vocabulary (Huang et al, 2013; Yanagisawa & Webb, 2021). Additionally, two meta-analyses focused on the overall predictive ability of the ILH and indicated that while the ILH significantly predicts vocabulary acquisition, its predictive power is relatively weak, explaining only about one-third of the variance in incidental vocabulary acquisition and retention (Liu & Reynolds, 2022; Yanagisawa & Webb, 2021). These findings suggest that while the ILH serves as a useful framework, there may be additional factors beyond task-induced involvement that influence vocabulary acquisition.…”
Section: Literature Reviewmentioning
confidence: 99%